Feedback reshapes the baryon distribution within haloes, in halo outskirts, and beyond: the closure radius from dwarfs to massive clusters - Ayromlou, Mohammadreza; Nelson, Dylan; Pillepich, Annalisa (Monthly notices of the Royal Astronomical Society, 2023)
We explore three sets of cosmological hydrodynamical simulations, IllustrisTNG (TNG50, TNG100, and TNG300), EAGLE, and SIMBA, to investigate the physical processes impacting the distribution of baryons in and around haloes across an unprecedented mass range of 10 ^8 < M200c/M < 1015, from the halo centre out to scales as large as R200c. We demonstrate that baryonic feedback mechanisms significantly redistribute gas, lowering the baryon fractions inside haloes while simultaneously accumulating this material outside the virial radius. ...
Online veröffentlicht am 8. Juli 2023
Gesehen am 14.12.2023